Effect of using fresh palm oil and used palm oil as a fat liquoring agent to the chemical quality of leather from tilapia fish skin - Pertiwiningrum, A.; Nugroho, K. E.; Roufi, M. A. N.; Parameswari, A. A.; Pastawan, V. (2022)
Tilapia skin has a high value in the form of tanned tilapia skin. One of the factors that play an important role in the tanning process is the using of tanning agents. This research was carried out by vegetable tanning to the tilapia fish skin using selected concentration of fresh palm oil and used palm oil. The study aims to find out the chemical quality of leather through the using of fresh and used palm oil as fat liquoring agent in the vegetable tannery process. The same concentration of fresh palm oil (10%), and used palm oil (10%) were used in this study. The parameter of fat content, and water content as chemical quality was observed in triplicates. Based on the results, the fat content of the leather using fresh palm oil (19.265%) was significantly increased (p<0.05) compared to used palm oil (15.825%), while the water content was also significantly different (p<0.05). In conclusion, the addition of palm oil improved the moisture of tilapia fish skin and become softer that can be used for commercial products, and it became the alternative material that could be use in vegetable tannery processing.